Normal Platelet Activation Profile in Patients with Peripheral Arterial Disease on Aspirin. Issue 3 (March 2015) - van Geffen, Johanna P.; Kleinegris, Marie-Claire; Verdoold, Remco; Baaten, Constance C.F.M.J.; Cosemans, Judith M.E.M.; Clemetson, Kenneth J.; ten Cate, Hugo; Roest, Mark; de Laat, Bas; Heemskerk, Johan W.M.
Abstract: Background: Peripheral arterial disease (PAD) is a progressive vascular disease associated with a high risk of cardiovascular morbidity and death. Antithrombotic prevention is usually applied by prescribing the antiplatelet agent aspirin. However, in patients with PAD aspirin fails to provide protection against myocardial infarction and death, only reducing the risk of ischemic stroke. Platelets may play a role in disease development, but this has not been tested by proper mechanistic studies. In the present study, we performed a systematic evaluation of platelet reactivity in whole blood from patients with PAD using two high-throughput assays, i.e. multi-agonist testing of platelet activation by flow cytometry and multi-parameter testing of thrombus formation on spotted microarrays. Methods: Blood was obtained from 40 patients (38 on aspirin) with PAD in majority class IIa/IIb and from 40 age-matched control subjects. Whole-blood flow cytometry and multiparameter thrombus formation under high-shear flow conditions were determined using recently developed and validated assays. Results: Flow cytometry of whole blood samples from aspirin-treated patients demonstrated unchanged high platelet responsiveness towards ADP, slightly elevated responsiveness after glycoprotein VI stimulation, and decreased responsiveness after PAR1 thrombin receptor stimulation, compared to the control subjects. Most parameters of thrombus formation under flow were similarly high for the patient and control groups. However, in vitro aspirin treatment caused a marked reduction in thrombus formation, especially on collagen surfaces. When compared per subject, markers of ADP- and collagen-induced integrin activation (flow cytometry) strongly correlated with parameters of collagen-dependent thrombus formation under flow, indicative of a common, subject-dependent regulation of both processes. Conclusion: Despite of the use of aspirin, most platelet activation properties were in the normal range in whole-blood from class II PAD patients. These data underline the need for more effective antithrombotic pharmacoprotection in PAD. Highlights: Whole-blood assays were used to evaluate platelets function in PAD patients. Platelet activation parameters by flow cytometry and thrombus formation correlated. Aspirin treatment in these patients did not lead to reduced platelet activation.